1821 Tenn. Pub. Acts 63, An Act to Amend the Militia Laws of This State, ch. 55, §§ 2-3. - (:unkn) unknown (My University, 1821)
§ 2. [T]he commissioned and staff officers of the infantry are hereby required to meet at the place of§holding their battalion musters at eleven o'clock on the day preceding said muster, armed with a rifle, musket, or shot gun and dressed§in the uniform prescribed by law, for the purpose of being trained as§at regimental drills, and the commanding or senior officer present shall call, or cause the roll to be called, and make a return of all delinquents to the next regimental or battalion court martial. § 3. That regimental courts martial shall have power to fine delinquents, field or staff officers, and it shall be the duty of the commanding or senior officer present at any regimental,§battalion or drill muster, to make a return of all such delinquents to the next regimental or battalion court martial, and they shall have a discretionary power to assess fines or not as they may think proper on delinquents.
Keywords: ARMED FORCES